Therapeutic Efficacy of Heterogenous Immunoglobulin in Canine Parvovirus Infected Dogs - Patil, Mrugali D; Waghmare, Sunil P; Pajai, Kishor S; Dighe, Dhananjay G; Kamdi, Bhupesh P; Bhasme, Sarang D (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted to assess the efficacy of heterogeneous immunoglobulin @ 0.4 mL/kg body weight per day intravenously along with supportive conventional therapy in CPV infected 10 puppies till recovery. One additional group of 10 normal healthy dogs was kept as a control group. CPV infection was diagnosed on the basis of clinical signs, rapid CPV antigen test kit and PCR assay. The clinical, haemato-biochemical parameters were investigated before and 7th day after treatment. The clinical study showed significant rise in rectal temperature, heart rate, respiratory rate and CRT in CPV infected dogs. The haemato-biochemical investigation showed significant decrease in Hb, TEC and increase in PCV and absolute neutrophil count together with significant decrease in serum total protein, albumin, globulin, creatinine, sodium and potassium, whereas, increase in BUN in parvovirus infected dogs. The study concluded that the treatment with injection heterogeneous immunoglobulins i/v with supportive conventional treatment found effective in inducing complete clinical recovery within 7 day of treatment along with improvement in altered haemato-biochemical parameters without any mortality in parvovirus infected puppies.